2020
DOI: 10.1115/1.4044900
|View full text |Cite
|
Sign up to set email alerts
|

Erosion in a Melt-Infiltrated SiC/SiC Ceramic Matrix Composite

Abstract: Erosion phenomenon of ceramic matrix composites (CMCs), attributed to their unique architectural configurations, is markedly different from conventional monolithic ceramic counterparts. Prior to further integration of CMCs into hot-section components of aeroengines subject to erosive environments, their erosion behavior needs to be characterized, analyzed, and formulated. The erosion behavior of a 2D woven melt-infiltrated (MI) SiC/SiC CMC was assessed in this work as a function of variables such as particle v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…It has been reported in the literature [34,35] that the erosion rate is proportional to the velocity according to a power law relationship where "n" is the exponent of the power law. At room temperature, the n for SiC-based ceramics has been found to be~2, which corresponds to brittle fracture mechanisms [33][34][35]. It was found in [27] that n was two at room temperature for these SA-MI composites.…”
Section: Use Of Hvof Burner Rig To Understand High Temperature Particle Erosionmentioning
confidence: 92%
See 1 more Smart Citation
“…It has been reported in the literature [34,35] that the erosion rate is proportional to the velocity according to a power law relationship where "n" is the exponent of the power law. At room temperature, the n for SiC-based ceramics has been found to be~2, which corresponds to brittle fracture mechanisms [33][34][35]. It was found in [27] that n was two at room temperature for these SA-MI composites.…”
Section: Use Of Hvof Burner Rig To Understand High Temperature Particle Erosionmentioning
confidence: 92%
“…Such conditions can result in hard particle erosion or molten deposition onto CMC and/or CMC/EBC materials. For hard particle erosion, considerable work has been performed by Choi and coworkers on many different substrate materials at room temperature [32,33]. However, no work had been performed at an elevated temperature.…”
Section: Use Of Hvof Burner Rig To Understand High Temperature Particle Erosionmentioning
confidence: 99%
“…9,[12][13][14][15][16][17][18][19][20][21][22] However, until recently, little work has been performed on characterizing and understanding the SPE behavior of CMCs and EBCs. [1][2][23][24][25][26] Conversely, extensive work has been performed on superalloys and TBCs. [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] In fact, SPE of superalloys and TBCs remains an area of active research.…”
Section: Dustmentioning
confidence: 99%
“…Material removal due to the repeated impact of solid particles, termed solid particle erosion (SPE), is a common phenomenon that is observed in both the cold and hot sections of gas turbine engines operating in particulateladen environments. [1][2][3][4] SPE is of particular concern for military aircraft which often operate in harsh, erosive environments, [1][2] but the phenomenon is also encountered by commercial aircraft. [3][4] SPE in gas turbine engines can occur while taxiing or during takeoff due to the ingestion of particulates from the runway, or at altitude as a result of airborne particles.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al propose that the impacting angle has a substantial influence on the mechanism's erosion [33]. Presby et al [34] and Panakarajupally et al [35] research outcome has identified the role of particle speed in erosion rate. Sharma et al examined at how concentration and particle interface influenced erosion rate and concluded that both factors had a large effect [36].…”
Section: Literature Reviewmentioning
confidence: 99%